Determination of Management Service Rewards in LMKN - Ernawaty Arthur Roida; Rudolf Lumbantobing; Soegeng Wahyoedi (Enrichment : Journal of Management, 2023)
The percentage of service fees used as LMKN operational costs often changes, this causes many problems. Particularly in terms of determining performance, as well as in terms of non-compliance with financial and tax reports. This study aims to find the best way to determine service costs that can cover operational activities consistently, as a non-profit institution that is responsible the rights owner’s prosperity. Through the interviews it can be concluded that the fee method which uses tariffs is indeed inconsistent, most of the informants gave suggestions using real costs, where all operational costs must be covered from the royalties collected before being distributed. To maintain the amount, a budget that has been agreed upon by stakeholders must be prepared. The budget includes short-term and long-term budgets, to facilitate activities that are quite expensive. The pattern of determining the compensation for this service can be regulated in the articles of association so that it cannot change along with the term of office of the commissioners at the LMKN. The initial determination of the budget can use historical data calculations with the high and low method, we can find the equation and the size of the budget to make the initial budget. From here we can standardize the form of recording and reporting both financial and tax statements. Performance can also be measured, to what extent the use of funds can generate benefits in accordance with the mission of the institution. The method that is considered appropriate for determining the amount of compensation for services so that it can cover operational costs at the LMKN is to bear the whole (real cost) of the proceeds from collecting royalties without using a percentage limit. The budget that must be made as a limitation of the use of costs. The budget must be approved by all stakeholders, both from the activities offered as well as from the amount of value. The financing method by bearing the real cost will reveal the problems that have occurred so far, the bookkeeping will be more consistent, because costs will only come out based on the approved budget.